Keberlanjutan Pendidikan dalam Upaya Peningkatan Kualitas Sumber Daya Manusia di Era Globalisasi - Syaifulloh, Muhammad; Yugo, Tri; Muhardi, Muhardi (CV. Publikasi Indonesia, 2025)
Sustainable education plays an important role in improving the quality of human resources (HR) in the era of globalization. This study aims to analyze the concept and application of education sustainability in an effort to improve the quality of human resources, as well as identify factors that affect education sustainability and the policies that support it. The approach used in this study is descriptive with a literature review method, by collecting data from scientific journals, official government reports, and related articles. The results of the study show that the sustainability of education does not only depend on academic quality, but also on the development of individual skills, character, and adaptability to changing times. Continuing education must be responsive to rapid technological, economic, and social developments. In this case, education policies that support improving the quality of teachers, equitable access to education, and integrating technology are important factors in achieving the goal of quality and inclusive education. The Indonesian government has implemented various policies, such as teacher certification programs, continuous training, and teacher professional development to improve the competence of educators. However, the main challenges faced are the gap in access to education between regions, as well as the need to adapt the curriculum to technological developments and the job market. This study concludes that the sustainability of education is an important long-term investment in shaping a generation that is ready to compete at the global level.